Characterizing the production process: A disaggregated analysis of Italian manufacturing firms - Giulio Bottazzi; Marco Grazzi; Angelo Secchi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2005)
This paper provides a description of the production process by comparing different frameworks in which to analyze the relations between inputs and output. The analyses are performed on a representative sample of Italian manufacturing firms. We employ both parametric and non-parametric analysis. The latter allows to detect the presence of heterogeneity in the way the production is carried out within each sector. Results of the econometric analysis show that coefficient estimates tend to be robust with respect to the different models employed.
Keywords: C1; L2; L6; 330; Input Output Relation; Panel Data; Returns to Scale; Labor Productivity; Prozessmanagement; Produktionsfunktion; Produktivität; Industrie; Italien